2018
DOI: 10.1002/aenm.201801804
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Plasma in Energy Conversion and Storage Materials

Abstract: Renewable energy sources such as solar, wind, and hydro hold the promise to meet the huge energy demands of the future at no environmental cost. Harvesting and utilization of these energies require efficient and low cost energy conversion and storage devices, whose performance essentially depends on the properties of the electrode materials. The properties of materials are greatly affected by synthesis methods and can be tuned by chemical modifications. Many approaches have therefore been developed toward this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 273 publications
(349 reference statements)
1
79
0
Order By: Relevance
“…In this work, we report a nickel‐iron‐molybdenum (NiFeMo) electrocatalyst with ultrafine metallic nickel domains of about 2.8 nm size and high‐valence reduced molybdenum ions (Mo 4+ ) on its surface, where have been prepared through the highly reducing chemicals using hydrogen and nitrogen plasmas. Also, NiFeMo oxyhydroxides have been directly grown on the 3D porous nickel foam substrate playing as an electron collector without using any binder.…”
mentioning
confidence: 99%
“…In this work, we report a nickel‐iron‐molybdenum (NiFeMo) electrocatalyst with ultrafine metallic nickel domains of about 2.8 nm size and high‐valence reduced molybdenum ions (Mo 4+ ) on its surface, where have been prepared through the highly reducing chemicals using hydrogen and nitrogen plasmas. Also, NiFeMo oxyhydroxides have been directly grown on the 3D porous nickel foam substrate playing as an electron collector without using any binder.…”
mentioning
confidence: 99%
“…Energy storage and conversion involve electrochemical processes that are directly driven by electrons at the electrode materials, such as nanocarbons, transition metal compounds, and metal nanocrystals. 8 As a result, the local electronic configurations of electrode materials play a pivotal role in determining their performance. [51][52][53] Recent advances have revealed that structural defects and heterostructures are of paramount importance in regulating the electronic configurations.…”
Section: Laser-mediated Structural Regulation Of Energy Materialsmentioning
confidence: 99%
“…[5][6][7] Because of the intermittency and geographical dispersion of these resources, electrochemical energy storage and conversion systems are of paramount importance for their efficient utilization. 8 In a reliable sustainable system, electricity generated from these renewable sources can either be directly stored in rechargeable batteries and supercapacitors as power supplies or be first converted into clean fuels via electrolyzers and then reproduced as electricity through fuel cells on demand. 5,8 Although these devices operate using different mechanisms, they employ similar device configurations whereby two separated electrodes are ionically connected by electrolytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photocatalytic has high potential as a green route for the hydrogen production even though it has the lowest efficiency . Biohydrogen can achieve energy efficiency levels more than 50% than electrolysis, but they have high acidification potential as a result of coemission SO 2 and the possible quantities of inorganics and/or ash . In summary, alkaline water analysis should become alternative technology nowadays even though it is nongreen hydrogen to hydrogenate CO 2 .…”
Section: Clean Hydrogen Production Technologiesmentioning
confidence: 99%